Community Based Medical Education – Necessity Realization and Practice - Koju, R (Kathmandu University Medical Journal, 2015)
DOI: http://dx.doi.org/10.3126/kumj.v11i3.12501 Kathmandu University Medical Journal Vol.11(3) 2013: 189-190